Erratum: Achieving a low-carbon future through the energy-chemical nexus in China (Sustainable Energy Fuels (2020) 4 (6141–6155) DOI: 10.1039/D0SE01337D) - Li, Yinan (Royal Society of Chemistry, 2022)
10.1039/d1se90060a